"A Different Kettle of Fish": Mental health strategies for Australian fishers, and farmers. (October 2015) - King, Tanya; Kilpatrick, Sue; Willis, Karen; Speldewinde, Christopher
Abstract: Despite being typically represented and managed under the same policy umbrella, fishers face different challenges than do their farming counterparts. This paper unpacks the findings of research depicting poor levels of mental health and well-being among Australian commercial wild-catch fishers. The research is considered in the context of widespread acceptance that farmers tend to exhibit worse than average mental health outcomes due, at least in part, to the environmental uncertainties of climate change. In particular it is stressed that the insecurity of fishing concessions (quota and licenses), is a key driver of chronic livelihood insecurity, resulting in reports of stress, depression and suicide. A call is made for the separation of health research in the fishing and farming industries. Importantly, the role that tenure insecurity plays in the perpetuation of poor mental health among fishers should be acknowledged and addressed so that the fishing industry can maximize the strength of its human capital. Highlights: Australian fishers exhibit poor mental health. Fishers and farmers are managed under the same policy umbrella. Insecure tenure renders fisher livelihoods insecure. Insecure livelihoods contribute to poor mental health. Separate consideration of fisher and farmer health challenges required to enable fisher health.